Modifikasi Kulit Telur Ayam Dan Serbuk Besi Sebagai Katalis untuk Reaksi Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Delvi Yolanda; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Eggshells modificated of solid base catalyst through calcination, hydration, dehydration methods with iron powder through impregnation method to load calcium oxide with eggshells as precursor. Effect of dehydration temperature and time on the catalytic performance were studied. The catalyst with the highest activity is obtained when the dehydration temperature of 600 °C and the dehydration time of 2 hours under transesterification reaction conditions of a molar ratio of methanol/oil 10:1, catalyst dosage of 1% by weight, temperature of 70 °C for 2 hours with yield biodiesel results reached 90%.Keywords: biodiesel, calcination, calcium oxide, catalysts, dehydration, hydration, impregnation, iron powder, transesterification.